Туризм как показатель качества жизни россиян в период кризиса - С.В. Дусенко (S.V. Dusenko) (Туризм и гостеприимство, 2016)
В статье автор анализирует развитие туризма в Российской Федерации в период разразившегося социально–экономического кризиса, перспективы развития внутреннего туризма. Автор справедливо доказывает, что, несмотря на кризис и в сфере политики, спрос на отдых и путешествие у россиян не ослабевает. Заметна активная тенденция развития внутреннего туризма в России. Ключевые слова: качество жизни, социально–экономический кризис, туризм. In article the author analyzes the development of tourism in the Russian Federation in the period of the unfolding socio–economic crisis, prospects of development of domestic tourism. The author rightly argues that, despite the crisis in the realm of politics, the demand for leisure and travel among Russians continues unabated. A noticeable trend is the active development of domestic tourism in Russia. Key words: quality of life, socio–economic crisis, tourism.